A Study on Consumer Attitude Towards Smoking Amongst Males and Females of Gen. Z in Ahmedabad - Gupta, Kopal; Patel, Prashant; Vidani, Jignesh (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
This research paper provides the valuable insights on the consumer behaviour towards smoking in Ahmedabad by focusing on both gender [ males and females]. We have conducted the survey to gather the insights into habits and awareness related to smoking. This survey involves various types of people like students going school and colleges, office going males and females of Gen. Z. This study involves the main reason of starting smoking are they all have same reason or problem for which they have started. The sampling method we have used here stratified sampling technique that ensures covers participants from different socio-economic backgrounds within Ahmedabad. The factors we have taken into consideration are attitudes towards smoking, why it became their habit, and peoples reviews and recommendation for starting campaign or programs related to less consumption of smoking. Analysis done that shows that people of 21-25 smoke more because the main reason overall we got is the pressure and stress. The future scope for the research is to reduce the percentage of people who are currently and formally smoking by running a campaign or short and comedy programs. This study is not only focused of present situation pf consumer attitude towards smoking but to provide foundation for better future analysis in this field in Ahmedabad city. The outcomes we expected is the percentage of people smoking should reduced to low they understand the harmfulness behind smoking and stop it.